Real time traffic density measurement using computer vision and dynamic traffic control - Chowdhury, Md. Fahim; Biplob, Md Ryad Ahmed (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.